Serial Killers: cinema e representação - Matos, Daniel Ivori de (2012)
In this study we intend, through film analysis, to understand how the movie industry has represented the Serial Killers, discussing the aspects that compose it and that constituted diverse views on the subject. Immediately film analysis led us to reflect on representations spread over the years about the Serial Killers, for better understanding of what aspects are present in these productions and appearing in the social imaginary. To this problematization noting as cinema dialogue with the cinema itself, in addition to treating social characteristics that are actually identified as belonging to these individuals, that is, showing how the film itself through the decades approached this subject. Therefore, we propose a study of image analysis that seeks to understand how the movie industry represents some questions, thus revealing aspects that make up an imaginary cast often by violent scenes of murders that boost the attendance of crowds to theaters. In this study will seek an analysis of how serial killers are represented in film, or are prepared to note how the representations of these individuals in the social imaginary and that impacts and changes caused by the strategies of language/esthetics of narrative film, so that the film turned out to be the main reference on the subject.